2021
DOI: 10.1016/j.cub.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for food texture preference based on grittiness

Abstract: Highlights d Flies prefer feeding on foods containing particles of a certain size d Sensation of particles in food depends on the OSCA/TMEM63 channel d TMEM63 detects particles in food through subtle deflections of taste sensilla d Mild deflections of sensilla require TMEM63 for activation of md-L neurons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Although TMEM63 proteins produce MS currents, their physiological roles remain largely unknown. A recent elegant study indicates that TMEM63 is crucial for the ability of flies to choose food based on particle size (Li and Montell, 2021). Typically, flies prefer foods with particle sizes that are typically found in fruits and budding yeast.…”
Section: Box 2 Caveats In Quantifying Ms Channel Currents In Drg Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TMEM63 proteins produce MS currents, their physiological roles remain largely unknown. A recent elegant study indicates that TMEM63 is crucial for the ability of flies to choose food based on particle size (Li and Montell, 2021). Typically, flies prefer foods with particle sizes that are typically found in fruits and budding yeast.…”
Section: Box 2 Caveats In Quantifying Ms Channel Currents In Drg Neuronsmentioning
confidence: 99%
“…This function is served by the mechanical activation of a subset of multidendritic neurons in the fly's major taste organ. Mutations disrupting TMEM63, but not other known MS channels including PIEZO, TMC, and NOMPC, abrogate the fly's ability to discriminate between food particle sizes (Li and Montell, 2021). Thus, TMEM63 is required for sensing small particles in food, which exert gentle mechanical forces on the labellum.…”
Section: Box 2 Caveats In Quantifying Ms Channel Currents In Drg Neuronsmentioning
confidence: 99%
“…For example, chocolate with a particle size above 35 μm is usually perceived as gritty or coarse in the mouth, and it is not accepted by consumers, nor is ice creams with ice crystals larger than 40 μm (Breen et al, 2019 ; De Pelsmaeker et al, 2020 ; Puleo et al, 2020 ; Servais et al, 2002 ). Interestingly, Li and Montell ( 2021 ) recently demonstrated that the Drosophila melanogaster is endowed with the ability to discriminate smoothness versus grittiness of food texture and uses this information to decide whether a food is appealing or not. One other angle here concerns the way that certain textures may be associated with specific taste qualities, as in the case of cotton candy/candy floss (see Spence et al, 2019 ).…”
Section: Food Texture Astringency and (Oral-somatosensory) Roughnessmentioning
confidence: 99%
“…The gustatory system (sense of taste) consists of approximately 5000 taste buds, each containing approximately 100 taste receptors onto which molecules bind. A mechanically activated TMEM63 channel allows sensing the texture of food [75].…”
Section: Some Human Abilitiesmentioning
confidence: 99%